AB0002 Analysis of nlrp3 and nod2 genes in adult onset still's disease. (23rd January 2014) - Garcia-Melchor, E.; Grados, D.; González-Roca, E.; Riera, E.; Juan, M.; Yagüe, J.; Arostegui, J. I.; Narváez, J.; Olivé, A.
Abstract : Background: Adult Onset Still's Disease (AOSD) is a systemic inflammatory disease characterized by fever, skin rash, articular involvement, lymphadenopathy, hepatosplenomegaly and serositis. Due to the absence of autoantibodies and autoantigen-specific T cells and the efficacy of treatment with IL-1β blocking agents, AOSD has been considered an autoinflammatory disease. Some entities of this group are inherited diseases caused by mutations in genes related with the processing of IL-1β. The cryopyrinopathies are caused by heterozygous gain-of-function mutations in NLRP3 gene (Nucleotide-binding domain Leucine Rich repeat family Pyrin domain containing 3) and share some clinical features with AOSD like fever, cutaneous and musculoskeletal involvement and serositis. Heterozygous gain-of-function NOD2 (Nucleotide Oligomerization Domain 2) mutations are associated with Blau syndrome, which is characterized by uveitis and, like AOSD, fever and chronic arthritis. Objectives: The aim of this study is to analyze the potential involvement of mutations in the NALP3 and NOD2 genes in AOSD patients. Methods: Eighteen patients with AOSD from two hospitals in Spain were enrolled. All the patients fulfilled the Yamaguchi criteria and informed consent was obtained from each participant. The study protocol was approved by the ethics committee from the Hospital Universitari Germans Trias i Pujol. Genomic DNA was extracted from whole blood using the Roche MagNAPure Compact (Roche Diagnostics, Indianapolis, IN). Exon 4 of NOD2 gene (GeneBank NM 022162.1) and exon 3 of NLRP3 gene (GeneBank NM 001243133.1) were amplified by polymerase chain reaction. Bidirectional fluorescence sequencing was performed using an ABI BigDye Terminator version 3.1 Cycle Sequencing kit and run on a 3730XL DNA Analyzer. As control population, the European Caucasic samples from 1000 Genome Project (n=379) were used. Differences in frequencies of alleles and genotypes between AOSD patients and controls were examined using the Chi-squared method, Fisher's exact test and logistic regression with Statistical Analysis Software (SAS). Results: Most AOSD patients showed no pathogenic variants in NALP3 or NOD2 gene. Of interest, two patients were carriers of a NOD2 polymorphism associated with Crohn disease (p.R702W, rs206684) without having any symptom suggestive of inflammatory bowel disease, and another one was carrier of a rare NOD2 variant of uncertain significance that was previously reported in a patient with spondyloarthritis (p.R791Q, rs104895464). In the NLRP3 analysis, one patient was carrier of the variant of uncertain significance p.V198M (rs121908147). Conclusions: AOSD has some similarities with inherited autoinflammatory syndromes like the clinical presentation and the efficacy of treatment with IL-1β blocking agents. Although in our series none of the AOSD patients carried a true disease-associated mutation, the possibility of an inherited autoinflammatory disease should be considered in the differential diagnosis and ruled out by means of genetic analysis. Disclosure of Interest: None Declared